Study the dynamic performance of PM machines for different rotor topologies - Abdullah K. Shanshal; Ahmed J. Ali; Alya H. AL-Rifaie (Institute of Advanced Engineering and Science, 2022)
For hybrid and electric vehicle drive-train (automotive applications) achieving high torque and efficiency at a wide range of operating conditions can be considered an important matter. Therefore, precise structure optimization of the permanent magnet synchronous machines (PMSMs) is recommended. Consequently, the effect of the main leading design parameters (such as PM arrangement, magnet thickness, pole arc to pole pitch ratio, airgap length as well as the effect of shaft material) for a different number of rotor poles configuration of PMSM can achieve optimum design results in electric motors with economical cost and excellent performance. This paper submits a comparative analysis of different rotor topologies of (PMSM). Moreover, the dynamic performances of the suggested rotor geometry topologies are investigated based on investigation of finite element analysis (FEA). The analysis offers a piece of complete information about the magnetic flux distribution and magnetic flux density over the motor geometry. Gained results from the analysis are used to give a decision for the selection of a suitable PMSM design.